ANALISA METODE SHA384 UNTUK MENDETEKSI ORISINALITAS CITRA DIGITAL - Simanullang, Putri M; Sinurat, Sinar; Saputra, Imam (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Cryptography is used to maintain the security of content or information that is personal from anyone except those who have the authority or secret key to open the information that has been encoded. Along with the development of technology and computers now, the increase in computer crime has also increased, especially in image manipulation. Many methods are used and carried out by people to manipulate images that have a detrimental effect on others. The originality of a digital image is the authenticity of the image in terms of colors, shapes, objects and information without the slightest change from the other party. Nowadays many digital images circulating on the internet have been manipulated and even images have been used for material fraud in the competition, so we need a method that can detect the image is authentic or fake like a diploma.In this study, the authors used the SHA-384 method to detect the originality of digital images, using this method an image that is still doubtful of its authenticity can be found out that the image is authentic or fake.Keywords: Originality, Citra, SHA-384